Microscale affinity purification of trypsin reduces background peptides in matrix-assisted laser desorption/ionization mass spectrometry of protein digests - Chamrád, Ivo; Strouhal, Ondřej; Rehulka, Pavel; Lenobel, René; Sebela, Marek (Journal of proteomics, 2011)
The use of trypsin for protein digestion is hampered by its autolysis and low thermostability. Chemical modifications have been employed to stabilize the enzyme. Modified trypsin (e.g. methylated) usually enables performing digestions at elevated temperatures, but it still produces autolytic peptides. In this work, unmodified bovine trypsin was subjected to a microscale affinity chromatography on Arginine Sepharose (ASE) or Benzamidine Sepharose (BSE), which utilized the principle of active-site ligand binding. Trypsin was retained on the sorbents in ammonium bicarbonate as a binding buffer. After washings to remove unbound impurities, the enzyme was eluted by arginine as a free ligand (from ASE) or by diluted hydrochloric acid (from BSE). MALDI-TOF mass spectrometry confirmed removal of large molecular fragments as well as autolytic and other background peptides. Consequently, the purified trypsin was tested for its performance in procedures of in-gel digestion of protein standards and selected urinary proteins from real samples. It has been shown that the affinity purification of trypsin decreases significantly the number of unmatched peptides in peptide mass fingerprints. The presence of arginine in the digestion buffer was found to reduce intensity of autolytic peptides. As a result, the described purification procedure is applicable in a common proteomic routine.
Keywords: Cattle; Proteinuria; Animals; skot; Electrophoresis, Polyacrylamide Gel; trypsin; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; proteinové hydrolyzáty; peptidové mapování; Peptide Mapping; mikrochemie; Protein Hydrolysates; Chromatography, Affinity; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Trypsin; zvířata; elektroforéza v polyakrylamidovém gelu; Microchemistry; chromatografie afinitní; proteinurie